Non-emerging adulthood helping parents of adult children with entrenched dependence - Dulberger, Dan 1962-; ʿOmer, Ḥayim 1949- (Cambridge University Press, 2021)
This book offers a therapeutic approach to a problem that many families and mental health institutions face: a growing number of adult children who struggle to progress to a psychological, social adulthood. The family patterns that revolve around adult children can remain inert for decades, are often resistant to conventional therapy, and can cause chronic suffering to adult children, parents, and extended families. The authors present a guide that addresses parents of adult children as suffering people in their own right and as essential to assisting their child into entering functional adulthood. The authors, one of whom is the originator of the Non-Violent Resistance Therapy approach (NVR), provide an intervention manual that implements NVR principles for helping families of adult children. The book is based on the authors' ten-year journey of helping such families in cases where traditional interventions and therapeutic values seem not to work